The reminding of environmental damage through salience patterns in Lorax (2012) film: An ecolinguistic analysis - Hadi, Muhammad Ihsan Nur; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This study analyzes the Lorax (2012) film through an ecolinguistic lens, focusing on salience patterns as a reminder of environmental degradation. The film portrays the consequences of excessive exploitation of nature using powerful visual and linguistic narratives. Applying Arran Stibbe’s framework, the research identifies linguistic elements such as activation, concreteness, metaphor, metonymy, hyponymy, and transitivity patterns that emotionally and ideologically highlight environmental issues. The findings reveal that Lorax not only delivers a moral message about the importance of environmental care but also fosters ecological awareness through its language use. This study affirms that ecolinguistics is a potent tool for uncovering hidden ideologies and promoting sustainable behavior through popular media.